Fenomena Komunikasi Dalam Membangun Konsep Diri Pada Mantan Pengguna Narkoba - Frista Fitriany Ramadhanita; Linda Loviana; Umi Rojiati (Jurnal Bimbingan Penyuluhan Islam, 2022)
ABSTRACT In this research, the writer wants to find out what is the role of the family so that the self-organization of former narcotics addicts is awakened. In a family where one of its members is addicted to drugs, this communication involves family members as the main tool for healing. And this research uses a qualitative case study methodology. the results of his research reveal that children are becoming more positive in their lives now, and are now able to socialize and their environment is willing to accept changes from former drug addicts as well as lead a productive and calm life.